2016
DOI: 10.5752/p.2175-5841.2016v14n41p48
|View full text |Cite
|
Sign up to set email alerts
|

Religious and Spiritual Struggles as Concerns for Health and Well-Being

Abstract: People struggle with religion and spirituality in several ways, including challenges in trusting God, confronting supernatural evil, tolerating other perspectives on religion, maintaining moral propriety, finding existential meaning, and managing religious doubt. These religious and spiritual (R/S) struggles relate to both physical and mental health independently of other religious and distress factors. Causality in this connection needs further study, but evidence supports many potential causes and moderators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 79 publications
2
46
0
Order By: Relevance
“…Religious persons may experience spiritual struggles, either related to the religious community, the doctrine or with God, and these struggles may affect their well-being (Exline and Rose 2013;Büssing et al 2013;Exline et al 2015;Stauner et al 2016). Related to God, religious persons may specifically experience that God is distant, is not responding to their prayers, feel abandoned by God, etc., resulting in spiritual 'dryness' and 'emptiness' (Büssing et al 2013, For SDAs, daily prayer and an unbroken relationship with God are the core of their spirituality (SDA Fundamental Belief Nr.…”
Section: Introductionmentioning
confidence: 99%
“…Religious persons may experience spiritual struggles, either related to the religious community, the doctrine or with God, and these struggles may affect their well-being (Exline and Rose 2013;Büssing et al 2013;Exline et al 2015;Stauner et al 2016). Related to God, religious persons may specifically experience that God is distant, is not responding to their prayers, feel abandoned by God, etc., resulting in spiritual 'dryness' and 'emptiness' (Büssing et al 2013, For SDAs, daily prayer and an unbroken relationship with God are the core of their spirituality (SDA Fundamental Belief Nr.…”
Section: Introductionmentioning
confidence: 99%
“…While religious comfort reflects personal benefits derived from faith, religious struggles are experiences of conflict or distress that refer to religious issues . Recent research has found links between religious struggles and reduced immune functioning, greater emotional distress, and depression …”
Section: Introductionmentioning
confidence: 99%
“…R/S struggles occur commonly, though not often severely [3,4]. A growing subdomain of psychological research on R/S examines the causes, consequences, and subjective experience of R/S struggle (for reviews, see [1,2,[5][6][7][8]). Over 80 new publications related to R/S struggle have appeared since the turn of the millennium [8].…”
Section: Introductionmentioning
confidence: 99%
“…A growing subdomain of psychological research on R/S examines the causes, consequences, and subjective experience of R/S struggle (for reviews, see [1,2,[5][6][7][8]). Over 80 new publications related to R/S struggle have appeared since the turn of the millennium [8]. Exline [1] reviewed the broad relationships between R/S struggle and health outcomes of both psychological and physical natures.…”
Section: Introductionmentioning
confidence: 99%